Efficient route towards the covalent functionalization of single walled carbon nanotubes - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Applied Surface Science, 2008)
A simple and efficient method of chemical functionalization of both single and multiwalled carbon nanotubes has been discussed to give enhanced water solubility by rapidly and efficiently generating an appreciable amount of hydrophilic functional groups using microwave radiation. Surface functionalization containing more than 30 wt% of oxygen has been achieved, resulting into solubility of 2-5 mg/mL. Further covalent functionalization of such soluble SWNTs provides a remarkable degree of aniline functionalization through amidation, where the formation of polyaniline has been avoided. Functionalization of SWNTs is confirmed by techniques like electron microscopy, Fourier transform infrared spectroscopy, thermogravimetry, Raman spectroscopy, cyclic voltammetry and impedance spectroscopy. Electrochemical analysis suggests an enhanced double layer capacitance (similar to 110 F/g) of nanotubes after microwave treatment. Aniline functionalization of SWNTs shows possible variations on the nanotube topography with concomitant formation of a dynamic polymer layer on the nanotube surface. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Functionalization; Microwave; solubility

Synthesis and thermal properties of soluble silicon containing phenylated aromatic-aliphatic polyamides - Ghanwat, A. A.; Sayyed, M. M.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Thermal Analysis and Calorimetry, 2009)
Aromatic polyamides find many applications in diverse and critical areas due to their high thermal stability coupled with high mechanical properties. However most of such aramides are difficult to fabricate because of their limited solubility and high melting temperature. Improvements in processability have been reported by incorporating bulky pendant groups and aliphatic spacer groups. Similarly to improve the solubility of polymers approaches of incorporating silicon in main polymer chain and co-polymerization techniques were useful. We report the synthesis and characterization of a series of phenylated silicon containing aromatic-aliphatic polyamides from a mixture of 2, 5-bis (4-carboxy methylene phenyl)-3, 4-diphenyl thiophene (CMPDT) and bis-(4-carboxy phenyl) dimethyl silane (BCPDS) in various mole proportions, with commercial aromatic diamine. Thus a series of novel co-polyamides having pendant phenyl groups, methylene spacer and silicon moiety was prepared by judicious combination of (CMPDT); BCPDS and aromatic diamine; bis-(4-aminophenyl) ether (ODA), by direct polycondensation using Yamazaki's phosphorylation method. These high molecular mass polyamides were obtained in high (89-98%) yields and had viscosities in the range of 0.23-0.57 dL/g in DMAc. Polyamides showed improved solubility in polar aprotic solvents, like NMP, DMAc, DMSO and DMF; had high thermal stability; with no mass loss below 335 A degrees C.
Keywords: 2; 4-diphenyl thiophene; 5-bis (4-carboxy methylene phenyl)-3; bis-(4-amino phenyl) ether; bis-(4-carboxy phenyl) dimethyl silane; Copolyamides; solubility; thermal stability

Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility

Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Synthesis and characterization of new organosoluble aromatic polyamides and polyazomethines containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2011)
New aromatic polyamides and polyazomethines containing pendent pentadecyl chains were synthesized by polycondensation of pentadecylbenzene-1,3-diamine with (i) four commercially available aromatic diacids, viz., biphenyl-4,4'dicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid and isophthalic acid, and (ii) dialdehydes, viz., terephthaldehyde, isophthaldehyde and a 50 : 50 mol% mixture of terephthaldehyde, and isophthaldehyde, respectively. Inherent viscosities of polyamides and polyazomethines were in the range 0.35-0.56 dL g(-1) and 0.33-0.38 dL g(-1), respectively, indicating the formation of medium molecular weight polymers. The presence of pendent pentadecyl chains in polyamides and polyazomethines led to an improvement in their solubility in organic solvents. Polyamides could be cast into flexible, transparent and tough films from their solution in N,N-dimethylacetamide while polyazomethines could be solution cast into transparent, flexible and stretchable films from their CHCl(3) solution. (1)H-NMR studies based on amide proton signals and azomethine proton signals indicated the presence of constitutional isomerism in the polyamides and polyazomethines. Wide-angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were amorphous in nature. X-ray diffractograms also displayed sharp reflections in the small angle region (2 theta approximate to 3 degrees) indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition (T(g)) temperatures of polyamides were in the range 169-215 degrees C while T(g) values for polyazomethines were in the range 16-55 degrees C. The temperature for the 10% weight loss of polyamides and polyazomethines were in the range 430-460 degrees C and 425-440 degrees C, respectively, in a nitrogen atmosphere, which indicated their good thermal stability. Polyazomethines were also characterized by UV-Vis and photoluminescence spectroscopy and optical band gap (E(g)) values, calculated according to the maximum of the UV absorption, were found to be in the range 2.82-3.10 eV.
Keywords: High performance polymers; optical band gap; polyamides; polyazomethines; solubility

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Water-promoted diels-alder reaction in quaternary ammonium salts - Nagare, Amit S.; Manna, Arpan; Sonawane, Pramod D.; Kumar, Anil (Journal of Physical Organic Chemistry, 2015)
{Prevailing classification of salts based on their effect in solubility and stability of proteins in aqueous solution predicts that tetraalkylammonium salts, guanidinium chloride (GnCl), LiClO4 act as salting-in (S/I) and LiCl, NaCl act as salting-out (S/O) in aqueous conditions. In the same context the behaviour of GnCl, LiClO4 and LiCl are contradictory in polar solvents like ethylene glycol and formamide. In these solvents, expected salt effect shows just opposite nature from their usual expectation. However, in the aqueous solution salts like tetraalkylammonium halide (R4NX
Keywords: Delta G(solvation); Diels-Alder reaction; k(s); kinetic study; solubility; tetraalkylammonium salts; viscosity

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability

Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine

Choline-amino acid-derived bio-ionic liquids for solubility enhancement of zafirlukast - Gaikwad, Namrata; Kudal, Swapna; Avachat, Amelia M. (AAPS Pharmscitech, 2022)
This study investigated the application of bio-ionic liquids (ILs) prepared from choline as cation and amino acid as anion for solubility enhancement of poorly water-soluble drug, Zafirlukast (ZFL). Herein, the solubility of ZFL in water and mixtures of water and ILs was assessed using UV spectroscopy at two temperature points 25 degrees C and 37 degrees C with increasing concentrations of IL. ZFL solubility was found to improve linearly with increasing concentration of [Ch][Pro] in water, representing 35- to 37-fold improvement in ZFL solubility at maximum concentration of [Ch][Pro] (1% w/v) compared to when only pure water was present. Also, the effect of IL on ZFL solubility was analyzed using NMR, DSC, and TGA. These results clearly suggest that ZFL solubility was increased by forming hydrogen bonds with selected [Ch][Pro] IL. Toxicity study of ILs was tested against gram-positive and gram-negative bacteria. Since IL solvent was found to increase the solubility of ZFL, this may serve as ``functional excipient solvent'' for solubility enhancement in its commercialized formulations.
Keywords: Amino acids; choline chloride; Ionic liquid; solubility; zafirlukast

Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility